Protective role of vitamin E against acrylamide-induced testicular toxicity from pregnancy to adulthood: insights into oxidative stress and aromatase regulation - Uremis, Muhammed Mehdi; Gultekin, Sevinc; Uremis, Nuray; Safak, Tarik; cigremis, Yilmaz; Gul, Mehmet; Turkoz, Yusuf (Springer, 2024)
Acrylamide (ACR) is a toxic chemical frequently encountered in daily life, posing health risks. This study aimed to elucidate the molecular-level mechanism of ACR's toxic effects on testicles and investigate whether Vitamin E can mitigate these effects. A total of 40 adult pregnant rats were utilized, divided into four groups: Control, ACR, Vitamin E, and ACR + Vitamin E. ACR and Vitamin E were administered to the mother rats during pregnancy and lactation, and to the male offspring until the 8th week post-birth. Serum hormone levels, oxidant-antioxidant parameters, histopathological examination of testicular tissue, and mRNA and protein levels of the testicular and liver aromatase gene were analyzed. Spermiogram analysis was conducted on the collected sperm samples from the male offspring. The results revealed that ACR exposure adversely affected hormone levels, oxidant-antioxidant parameters, histological findings, as well as aromatase gene and protein expressions. However, Vitamin E administration effectively prevented the toxic effects of ACR. These findings demonstrate that ACR application significantly impairs the reproductive performance of male offspring rats by increasing liver aromatase activity.
Keywords: Acrylamide; Testicle; Spermiogram; Aromatase; Oxidative stress